La “professionnalisation” des formations universitaires en France - Dominique Maillard; Patrick Veneau (Cahiers de la Recherche sur l'Education et les Savoirs)
This article studies how the idea of what is called today “vocationalisation” of university degrees emerged and evolved, and what meanings and contents have been associated to it. The process is analyzed at three levels: the national and political level where the term first appeared and took shape, the local level in charge of implementing it, then the level of teaching where it get its substance. If a convergence of principles can be observed between institutions, teachers and the national level, it remains that the form and contents of the “vocationalisation” – because it is part of a process of diversification – tend to shift away from the political ambition. The partnerships implemented within the framework of the “vocational degree” are an outstanding illustration.